Impact of hydatid cyst laminated layer antigens on cell death rate, apoptosis induction, and key genes in the cell proliferation pathway: Insights from A549 cell line studies - ElaheSadat Hosseini; Masoumeh Tavakoli-Yaraki; Ahmad Reza Meamar; Zeynab Ajam; Maryam Alipour; Ruchika Bagga; Elham Razmjou; Raheleh Rafiei-Sefiddashti (PLoS ONE, 2025)
While lung cancer remains a lethal disease despite treatment advances, some parasitic infections can demonstrate cancer-modulating roles and exhibit anti-tumor effects. The emergence of hydatid cysts as a potential anti-cancer treatment has sparked optimism for the development of more successful therapies. This research examines the effect of hydatic cysts on the growth and proliferation of lung tumor cells, as well as the underlying molecular mechanisms involved. The laminated layer (LL) of the hydatid cyst antigens was administered to lung cancer cells with varying dosages and durations. The MTT assay was applied to evaluate cell viability. After exposure to different concentrations of LL antigens, the apoptosis, necrosis, cell cycle, and intracellular reactive oxygen species (ROS) of the cell culture were measured using flow cytometry. The expression levels of SOX-9, β-catenin, CD133, and CD44 genes were assessed using Real-Time PCR. Treating A549 cells with varying concentrations of LL antigens resulted in a decrease in viable cells, which depended on both time and dosage. Treatment with cysts led to apoptosis induction and a reduction in necrosis percentage in a dose-dependent manner. The induction of apoptosis correlated with elevated ROS production and a notable decrease in the expression of invasion-related genes (β-catenin, CD133, and CD44) (P < 0.05). However, this reduction in expression was not statistically significant for SOX-9. Exposing lung cancer cells to precise amounts of crude LL antigens resulted in cell death, apoptosis, increased intracellular ROS levels, and reduced expression of genes linked to cancer cell growth and invasion. These results lay the groundwork for further exploring purified Echinococcus granulosus parasite antigens as potential drug targets in cancer treatment.